2007
DOI: 10.1074/jbc.m704349200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Yields Protein Arginine Methyltransferase 1 Isoforms with Distinct Activity, Substrate Specificity, and Subcellular Localization

Abstract: PRMT1 is the predominant member of a family of protein arginine methyltransferases (PRMTs) that have been implicated in various cellular processes, including transcription, RNA processing, and signal transduction. It was previously reported that the human PRMT1 pre-mRNA was alternatively spliced to yield three isoforms with distinct N-terminal sequences. Close inspection of the genomic organization in the 5-end of the PRMT1 gene revealed that it can produce up to seven protein isoforms, all varying in their N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
204
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(225 citation statements)
references
References 76 publications
17
204
1
3
Order By: Relevance
“…It has been reported that alternative splicing of the human PRMT1 primary transcript can give rise to at least three protein isoforms, and that their N-termini are different from one another. 44) Goulet et al 52) have further extended these findings, and have confirmed that the complex genomic organization of the 5 0 -end of the PRMT1 gene can produce up to seven protein isoforms, with molecular masses of 40.5, 42.5, 39.8, 40.1, 39.4, 37.7, and 36.7 kDa, designated v1-7 respectively, expressed in a tissue-specific manner. Our findings provide the first evidence that PRMT1 isoforms are expressed in a tissue-specific manner in the rat as well as the mouse and humans.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that alternative splicing of the human PRMT1 primary transcript can give rise to at least three protein isoforms, and that their N-termini are different from one another. 44) Goulet et al 52) have further extended these findings, and have confirmed that the complex genomic organization of the 5 0 -end of the PRMT1 gene can produce up to seven protein isoforms, with molecular masses of 40.5, 42.5, 39.8, 40.1, 39.4, 37.7, and 36.7 kDa, designated v1-7 respectively, expressed in a tissue-specific manner. Our findings provide the first evidence that PRMT1 isoforms are expressed in a tissue-specific manner in the rat as well as the mouse and humans.…”
Section: Discussionsupporting
confidence: 50%
“…As shown in Figure 2a, only wild-type (WT) GST-PRMT1 methylated the N-terminus of Axin, compared with dominantnegative GST-PRMT1 which has no enzymatic activity (McBride et al, 2000). PRMT1 is a type I arginine methyltransferase, a group that includes PRMT3, PRMT4/Carm1 and PRMT6 (Bedford and Clarke, 2009), and has several splicing variants (Goulet et al, 2007). Among them, PRMT1, PRMT3 and PRMT6 methylate substrates have a conserved glycine/argininerich (GAR) motif, whereas PRMT4/Carm1 has different motif (Boisvert et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The loss of PRMT1 increased the levels of MMA and SDMA, and PRMT1 is transported between the nucleus and cytoplasm depending on the methylation status of substrate proteins in several cells [21]. On the other hand, PRTM1 has some splicing variants, and the noncoding variant of PRMT1, PRMT1 variant 2, was reported to be associated with progression of both colon and breast cancer [13,22]. Moreover, it was reported that PRMT1 functions such as substrate recognition and methylation are inhibited by phosphorylation of Tyr291 [23].…”
Section: Discussionmentioning
confidence: 99%